(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Collaboration between doctors and nurses is fundamental to delivering high-quality dental care. This partnership involves leveraging complementary expertise, effective communication, and a patient-centered approach to address various challenges and opportunities in dental practice. Key aspects of collaboration include enhancing patient education, promoting preventive care, and addressing workload management and conflict resolution. By embracing collaboration, dental professionals can optimize patient outcomes, improve practice efficiency, and foster a culture of innovation and professionalism in dental healthcare.